The Effect of Mechanical Overloading on Surface Roughness of the Coronary Arteries - Hanna E. Burton; Daniel M. Espino (Applied Bionics and Biomechanics)
Background. Surface roughness can be used to identify disease within biological tissues. Quantifying surface roughness in the coronary arteries aids in developing treatments for coronary heart disease. This study investigates the effect of extreme physiological loading on surface roughness, for example, due to a rupture of an artery. Methods. The porcine left anterior descending (LAD) coronary arteries were dissected ex vivo. Mechanical overloading was applied to the arteries in the longitudinal direction to simulate extreme physiological loading. Surface roughness was calculated from three-dimensional reconstructed images. Surface roughness was measured before and after damage and after chemical processing to dehydrate tissue specimens. Results. Control specimens confirmed that dehydration alone results in an increase of surface roughness in the circumferential direction only. No variation was noted between the hydrated healthy and damaged specimens, in both the longitudinal (0.91±0.26 and 1.05±0.25 μm) and circumferential (1.46±0.38 and 1.47±0.39 μm) directions. After dehydration, an increase in surface roughness was noted for damaged specimens in both the longitudinal (1.28±0.33 μm) and circumferential (1.95±0.56 μm) directions. Conclusions. Mechanical overloading applied in the longitudinal direction did not significantly affect surface roughness. However, when combined with chemical processing, a significant increase in surface roughness was noted in both the circumferential and longitudinal directions. Mechanical overloading causes damage to the internal constituents of the arteries, which is significantly noticeable after dehydration of tissue.